The role of beliefs and expectations in predicting dating violence in adolescence - Sušac, Nika (Array, 2012)
A study on dating violence in adolescent romantic relationships was conducted with a sample of 12 grade students (N=1225 ; 52.7% male) from secondary schools throughout Croatia. The aim was to determine the contribution of different cognitive variables, such as beliefs and romantic expectations, in predicting perpetration of dating violence and victimization. Six questionnaires developed for this study were used: Beliefs about healthy romantic relationships (k=18 ; α=.73), Importance of own rights in a relationship (k=10 ; α=.82), Setting own boundaries (k=12 ; α=.94), Recognition of violent behaviors (k=26 ; α=.91), Victimization (k=30 ; α=.92) and Perpetration of dating violence (k=30 ; α=.92). The sociodemographic variables included: gender, type of school (vocational vs. grammar school), academic achievement and relationship duration. Hierarchical regression analyses with victimization and perpetration of dating violence as criterion variables were done. While controlling for other variables, the model that included male gender, inaccurate beliefs about relationships and higher importance of own rights predicted more frequent victimization (6.8% of variance explained), while longer duration of the relationship, inaccurate beliefs about relationships, higher importance of own rights and poorer recognition of violent behaviors predicted perpetration of violence (12.9% of variance explained). Some significant interactions between gender and other predictors were also observed. Introduction of victimization variable into the predictive model for perpetration substantially increased the amount of explained variance (49.1%).